Mathematical modelling appplied to the “Batch” milling process - Pérez M., Edgar A. (2017)
Mathematical modelling applied to batch milling (at experimental level), is a very important tool to simulate and predict the granulometric yield of a given treated ore; this means, for a given duration of milling operation, to obtain an estimate of the corresponding granulometric analysis, which can then be tested with real data later on, to verify the estimates. The model involves the selection and fracture functions depending on each mesh size in the ore distribution. This will allow the prediction of effective and reliable results, saving costs and more importantly, time, without the need to perform the milling process for each prediction of batch milling.